Vplyvy genetických faktorov na genézu a rast priecne pruhovaného kostrového svalového tkaniva - Makovický, P; Makovický, P; Kulísek, V (Ceskoslovenska fysiologie, 2007)
The growth is inseparable part of ontogenesis and simply is characterised as a biological process, which is outcome of internal and external changes and interaction of all organ systems. The striated skeletal muscles are developed during a prenatal period from mesoderm and individual development is finished in time of birth and also post partum. The basic sign of the last stage is a nuclei periphery movement from the centre under sarcolemma whereas myofibriles fill interior. Every individual muscular system consists of the specific particular type of muscle fibres, which were formed during embryogenesis. The nuclei of muscle fibres are postmitotic and it is evident, that only one way of muscle growth consists of coarsing and lengthening of existing muscle fibres. The muscle fibres growth and development is followed by various effects, which can be classified as genetic or other effects. By intensive studies of genetic effects was recognised that in muscles are presented not only tissular specific gene but also ubiquitous genes, which regulate processes of protein muscles and fat synthesis. The latest research exposed the existence of genes in muscles, which have influence to structural component of skeletal muscles. In present contribution we describe genetic factors effects to genesis and growth of the striated skeletal muscles.
Keywords: Transforming Growth Factor beta; Animals; vývoj svalů; kosterní svaly; kosterní svalová vlákna; lidé; hospodářská zvířata; zvířata; Animals, Domestic; MyoD Protein; transformující růstový faktor beta; Muscle Development; Muscle Fibers, Skeletal; Myostatin; myostatin; Muscle, Skeletal; Humans